Notes de lecture et édition du « second volume » de Bouvard et Pécuchet : configurations complexes de l’inachèvement - Stéphanie Dord-Crouslé (Flaubert: Revue Critique et Génétique)
Examining the preparatory documents allows to establish the regular pattern of development of the second volume of Bouvard et Pécuchet despite its incompleteness: Flaubert selects textual fragments on his reading notes pages before they are copied first on summary pages and then on pages prepared for the second volume. However some in absentia fragments (designated by Flaubert for the second volume, but not actually copied) pose complex editorial problems: the text referred to by the novelist should it be published? and if so, how to set it? Finally, even when following a regular pattern, the development process of the second volume is incomplete and it is impossible to know whether or not Flaubert would have kept the marks of enunciation that many copied citations include. These issues will be discussed in the context of the electronic edition of the documentary files for Bouvard et Pécuchet and of the production of second volumes on demand.